2014
DOI: 10.33899/rjs.2014.88652
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plant Seeds Peganum harmala Evaporation on Fertility of White Rats Male Treated with Drug Chlorpromazine

Abstract: The present study includes the investigation of the effect of evaporation with Peganum harmala seeds on hormone FSH, LH, testosterone concentrations and sperm count in male albino rats Rattus norvegicus treated with Chlorpromazine. The rats were aged (3-4) months and weighing (200-300) grams. The first group was a negative control of 10 rats which gavaged with distilled water and the 50 remaining rats gavaged with Chlorpromazine (2 mg / kg body weight) daily for six weeks. The treated animals were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similar observations were reported by El-Dwairi and Banihani [ 22 ] in rats treated for 60 days with P. harmala seeds extract. In another study, the research team members concluded that the evaporation of P. harmala seeds for 7, 14, and 21 days, respectively, caused an increased sperm count in male rats treated with chloropromazine [ 47 ]. Likewise, the in vitro addition of low concentrations of total alkaloids P. harmala seeds in the sperm produced stimulation of motility and protection against oxidative damages [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations were reported by El-Dwairi and Banihani [ 22 ] in rats treated for 60 days with P. harmala seeds extract. In another study, the research team members concluded that the evaporation of P. harmala seeds for 7, 14, and 21 days, respectively, caused an increased sperm count in male rats treated with chloropromazine [ 47 ]. Likewise, the in vitro addition of low concentrations of total alkaloids P. harmala seeds in the sperm produced stimulation of motility and protection against oxidative damages [ 48 ].…”
Section: Discussionmentioning
confidence: 99%